Relevancia de la implementación de la gestión del talento humano en las empresas - Paternina Rodríguez, Beltquis Patricia (Ciencias Administrativas, Económicas y Contables, 2017)
A fundamental prop inside the companies is the human talent, which offers to him his knowledge and skills for the manufacture of products or provision of services. For it, nowadays there have been developing internal strategies that motivate the employee to a better accomplishment of his work, in order which the company reaches his aims of an efficient and effective way. Bearing in mind that to carry out the management of the human talent can generate so much positive results as negative in any type of company commercial, industrial and of services, it is important to have a good execution in it.